HIV futures 8: Protocol for a repeated cross-sectional and longitudinal survey of people living with HIV in Australia - Power, J.; Brown, Graham; Lyons, A.; Thorpe, R.; Dowsett, G.; Lucke, J. (2017)
Â© 2017 Power, Brown, Lyons, Thorpe, Dowsett and Lucke. Introduction: More than 27,000 Australians currently live with HIV. Most of these people have access to quality clinical care and antiretroviral treatment (ART) and can expect good general health. However, HIV-related stigma is a problem and many people living with HIV experience poorer than average mental health. Issues of aging are also of increasing concern. This paper describes the methods and sample for the HIV Futures 8 study, a national survey of people living with HIV in Australia that aimed to identify factors that support health and well-being among this population. HIV Futures 8 forms part of a series of cross-sectional surveys (The 'HIV Futures' studies) that have been repeated periodically since 1997. In the most recent survey, participants were able to opt into a prospective longitudinal study. Materials and equipment: HIV Futures 8 was open to people aged over 17 who were living with HIV. Data were collected in 2015/2016 using a self-complete survey that contained approximately 250 items related to physical and mental health, use of ART, HIV exposure and testing, financial security, social connectedness, relationships, life satisfaction, resilience, stigma, use of health and support services, and health literacy. To enable comparison of cross-sectional data over time, questionnaire items were consistent with those used in previous HIV Futures surveys. In HIV Futures 8, participants were invited to volunteer coded information that will allow longitudinal follow-up when participants complete subsequent HIV Futures surveys. The survey was advertised through the networks of HIV organizations, on social media and through HIV clinics and services. HIV Futures 8 was completed by 895 participants. This represents approximately 3.8% of the total number of people living with diagnosed HIV in Australia in 2014. Expected impact of the study on public health: Findings from HIV Futures 8 will contribute important insights into the complexity of factors that support physical and mental well-being among people living with HIV. The findings will also assist HIV services to align with broader public health goals related to increasing ART use and improving quality of life among people living with HIV.